Characterization of enteroviruses circulating among farm animals and children in Central African Republic - Joël Doté; Marie-Line Joffret; Bertille Ndombari Beta; Mohand Ait-Ahmed; Virginie Banga-Mingo; Nick J. Knowles; Nolwenn Jouvenet; Marie-Noël MBaïkoua; Ionela Gouandjika-Vasilache; Maël Bessaud (Emerging Microbes and Infections)
To characterize enteroviruses (EVs) circulating in farm animals in Central African Republic (CAR), we screened 192 stools of animals under 12 months belonging to family farms located in or near Bangui. To assess whether EV exchanges exist between these animals and humans, we also screened 195 stools of children who lived in contact with farm animals, as well as control stools of 358 children with no contact with farm animals. EVs were typed based on their capsid sequences.In children, all EVs belonged to species A, B and C, with EV-Cs accounting for 60%. Some EV-Cs shared recent common ancestors with lineages of vaccine-derived poliovirus that emerged in the country in 2019–2020. In animals, we identified EV-Gs that belonged to 10 different types, including a previously unknown one that we named EV-G28, while no EV-E or EV-F were observed. The CAR EV-Gs were genetically closely related to specimens sampled in other continents and some of them harboured the torovirus-derived insertion already reported in some EV-Gs. The worldwide circulation of EV-Gs is likely due the massive international trade of live animals. Besides, two human EV-Cs (coxsackievirus A17 and coxsackievirus A24) were detected in pigs, suggesting that these viruses could cross the species barrier. Our work provides original data on the epidemiology and ecology of EVs circulating among herd animals in Africa.